Formulation of Ivermectin 1% Injectable Solution for Veterinary Use: Orooba M. S. Ibrahem1; Duraid A. Abbas1@ and Feryal. M2 - Abbas, Duraid A. (The Iraqi Journal of Veterinary Medicine, 2013)
New formulation of Ivermectin 1% injectable solution was prepared for Veterinary therapeutic use. Information about all the materials used in preparation of formula were collected from the pharmacopeia while analar material were provided and used to prepare about three pilot formulae, from which the final one was prepared. Stability of new formula was tested in different room environmental conditions by comparing any change in physicochemical properties concerning form, color, transparency, pH in different storage room temperatures for 20 months. The results of testing the formula both in-vitro against parasitic larvae motility and parasitic infection in diseased cattle and sheep indicating its efficiency as well as its chemical analysis, that indicate nearly no change in its concentrations for almost two years analysis. This formula was approved by I.V.S.C. as a drug for veterinary therapeutic uses after passing all testing schedule. A certificate for such was provided